Understanding behavior - Gleeson, M.B. (Introducing Autism: Theory and Evidence-Based Practices for Teaching Individuals with ASD, 2024)
Understanding behavior is paramount to educating and supporting individuals on the autism spectrum. This chapter provides an overview of applied behavior analysis including dispelling common misconceptions of the science, the ethics of behavior change, the process of completing a functional behavior assessment, including discussion on positive and negative reinforcement and the four functions of behavior, and using information gathered in a functional behavior assessment to plan supports for students. The chapter ends with an introduction to the evidence-based practice of antecedent-based interventions. © 2024 Taylor & Francis Group. All rights reserved.
Keywords: dept.sed